Human Rif1, ortholog of a yeast telomeric protein, is regulated by ATM and 53BP1 and functions in the S-phase checkpoint - Silverman, Joshua (Cold Spring Harbor Laboratory Press, 2004)
We report on the function of the human ortholog of Saccharomyces cerevisiae Rif1 (Rap1-interacting factor 1). Yeast Rif1 associates with telomeres and regulates their length. In contrast, human Rif1 did not accumulate at functional telomeres, but localized to dysfunctional telomeres and to telomeric DNA clusters in ALT cells, a pattern of telomere association typical of DNA-damage-response factors. After induction of double-strand breaks (DSBs), Rif1 formed foci that colocalized with other DNA-damage-response factors. This response was strictly dependent on ATM (ataxia telangiectasia mutated) and 53BP1, but not affected by diminished function of ATR (ATM- and Rad3-related kinase), BRCA1, Chk2, Nbs1, and Mre11. Rif1 inhibition resulted in radiosensitivity and a defect in the intra-S-phase checkpoint. The S-phase checkpoint phenotype was independent of Nbs1 status, arguing that Rif1 and Nbs1 act in different pathways to inhibit DNA replication after DNA damage. These data reveal that human Rif1 contributes to the ATM-mediated protection against DNA damage and point to a remarkable difference in the primary function of this protein in yeast and mammals.